PREPARATION OF CHITOSAN-GOLD NANOPARTICLES: PART 2. THE ROLE OF CHITOSAN - Adlim Adlim; Mohamad Abu Bakar (Universitas Gadjah Mada, 2008)
Colloidal gold nanoparticles prepared by employing chitosan as the stabilizer in solvent of methanol-acetic acid solution were stable for months without precipitation. The mole ratio of chitosan-gold ions of 5:1 - 30:1 gave dispersed and fine gold particles in range of 9.4-10.4 nm. Gold reduction in chitosan matrix was faster at higher chitosan concentration, and molar ratio of chi : Au, from 5:1 to 40:1. Higher acidity of acetic acid (pH 2-6) led to faster reduction of gold ions. The intensity of gold metal colloid plasmon band increased at higher concentration of acetic acid. Chitosan functioned both as a stabilizer and a reducing agent for gold ions. Gold colloidal particles immobilized on chitosan coated TiO2 as the solid support gave more dispersed and smaller particles (4.6 nm) compared with gold particles supported on TiO2 without chitosan coating.